Divergent growth chronologies of a deep-water snapper along a tropical continuum in northwestern Australia - Júlio Guazzelli Gonzalez; Clement Z. W. Ng; Muhammad Faiq Saleh; Corey B. Wakefield; Stephen J. Newman; Joyce Jia Lin Ong (Reviews in Fish Biology and Fisheries, 2026)

Childhood residential proximity to the radiologically contaminated Coldwater Creek and later-life cardiovascular disease in the St. Louis Baby Tooth study - Michael Leung; Joyce J.Y. Lin; Murray A. Mittleman; Justin G. Farmer; Ian W. Tang; Kaleigh McAlaine; Joseph J. Mangano; Marc G. Weisskopf (Science of The Total Environment, 2026)

Prenatal and early postnatal lead exposure and later adulthood BMI: The Saint Louis baby tooth – Later life health study - Joyce J.Y. Lin; Ruby Hickman; Michael Leung; Justin Farmer; Ian W. Tang; Kaleigh McAlaine; Tracy Punshon; Brian P. Jackson; Felicitas B. Bidlack; Joseph J. Mangano; Marc G. Weisskopf (Environmental Research, 2026)

Mechanisms of reentry arrhythmia termination with ephaptic coupling and gap junctional coupling - Ning Wei; Joyce Lin (Journal of Theoretical Biology, 2026)

Temperature and carotid intima-medial thickness: The coronary artery risk development in young adults (CARDIA) study - Brian T. Joyce; Jie Yao; Yinan Zheng; Tao Gao; Drew Nannini; Shao Lin; Xin Li; Jaymie Meliker; Qianqian Song; David R. Jacobs; Donald Lloyd-Jones; Lifang Hou; et al. (Science of The Total Environment, 2024)

Residential Proximity to Metal-Emitting Industries and Toenail Metal Concentration in the US Gulf States - Joyce J. Y. Lin; Emily J. Werder; Kaitlyn G. Lawrence; W. Braxton Jackson; Dale P. Sandler; Aisha S. Dickerson; Lawrence S. Engel; Ana M. Rule (Exposure and Health, 2024)

Critical infrastructure organisational resilience assessment: A case study of Malawi’s power grid operator - Joyce Nyuma Chivunga; Zhengyu Lin; Richard Blanchard (The Electricity Journal, 2024)

Associations of a toenail metal mixture with attention and memory in the Gulf long-term follow-up (GuLF) study - Joyce J.Y. Lin; Jordan R. Kuiper; Aisha S. Dickerson; Jessie P. Buckley; Heather E. Volk; Diane S. Rohlman; Kaitlyn G. Lawrence; W. Braxton Jackson; Dale P. Sandler; Lawrence S. Engel; Ana M. Rule (Science of The Total Environment, 2024)

The conduction velocity-potassium relationship in the heart is modulated by sodium and calcium - D. Ryan King; Michael Entz; Grace A. Blair; Ian Crandell; Alexandra L. Hanlon; Joyce Lin; Gregory S. Hoeker; Steven Poelzing (Pflügers Archiv - European Journal of Physiology, 2021)
The relationship between cardiac conduction velocity (CV) and extracellular potassium (K + ) is biphasic, with modest hyperkalemia increasing CV and severe hyperkalemia slowing CV. Recent studies from our group suggest that elevating extracellular sodium (Na + ) and calcium (Ca 2+ ) can enhance CV by an extracellular pathway parallel to gap junctional coupling (GJC) called ephaptic coupling that can occur in the gap junction adjacent perinexus. However, it remains unknown whether these same interventions modulate CV as a function of K + . We hypothesize that Na + , Ca 2+ , and GJC can attenuate conduction slowing consequent to severe hyperkalemia. Elevating Ca 2+ from 1.25 to 2.00 mM significantly narrowed perinexal width measured by transmission electron microscopy. Optically mapped, Langendorff-perfused guinea pig hearts perfused with increasing K + revealed the expected biphasic CV-K + relationship during perfusion with different Na + and Ca 2+ concentrations. Neither elevating Na + nor Ca 2+ alone consistently modulated the positive slope of CV-K + or conduction slowing at 10-mM K + ; however, combined Na + and Ca 2+ elevation significantly mitigated conduction slowing at 10-mM K + . Pharmacologic GJC inhibition with 30-μM carbenoxolone slowed CV without changing the shape of CV-K + curves. A computational model of CV predicted that elevating Na + and narrowing clefts between myocytes, as occur with perinexal narrowing, reduces the positive and negative slopes of the CV-K + relationship but do not support a primary role of GJC or sodium channel conductance. These data demonstrate that combinatorial effects of Na + and Ca 2+ differentially modulate conduction during hyperkalemia, and enhancing determinants of ephaptic coupling may attenuate conduction changes in a variety of physiologic conditions.

Discrimination of Tourette Syndrome Based on the Spatial Patterns of the Resting–State EEG Network - Keyi Duan; Qian Wu; Yuanyuan Liao; Yajing Si; Joyce Chelangat Bore; Fali Li; Qin Tao; Li Lin; Wei Lei; Xudong Hu; Dezhong Yao; Changfu Pei; et al. (Brain Topography, 2021)

Potassium channels in the Cx43 gap junction perinexus modulate ephaptic coupling: an experimental and modeling study - Rengasayee Veeraraghavan; Joyce Lin; James P. Keener; Robert Gourdie; Steven Poelzing (Pflügers Archiv - European Journal of Physiology, 2016)

Extracellular sodium and potassium levels modulate cardiac conduction in mice heterozygous null for the Connexin43 gene - Sharon A. George; Katherine J. Sciuto; Joyce Lin; Mohamed E. Salama; James P. Keener; Robert G. Gourdie; Steven Poelzing (Pflügers Archiv - European Journal of Physiology, 2015)

Sodium channels in the Cx43 gap junction perinexus may constitute a cardiac ephapse: an experimental and modeling study - Rengasayee Veeraraghavan; Joyce Lin; Gregory S. Hoeker; James P. Keener; Robert G. Gourdie; Steven Poelzing (Pflügers Archiv - European Journal of Physiology, 2015)

Tissue factor expression in ovarian cancer: implications for immunotherapy with hI-con1, a factor VII-IgGFc chimeric protein targeting tissue factor - Emiliano Cocco; Joyce Varughese; Natalia Buza; Stefania Bellone; Ken-Yu Lin; Marta Bellone; Paola Todeschini; Dan-Arin Silasi; Masoud Azodi; Peter E. Schwartz; Thomas J. Rutherford; Luisa Carrara; et al. (Clinical & Experimental Metastasis, 2011)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)